Verification of Conceptual Architecture Based on Component - Chao Ji; Qi Chen; Xin He; Guanglei Qi (2010 International Conference on Computational Intelligence and Software Engineering, 2010)
At present, few methods of creating conceptual architecture have been proposed. What's more, they can't meet the requirements of dynamic Internet environment or software reuse. However, a newly proposed method in paper can adapt to various types of changes in the dynamic environment and can make design and implementation more convenient than traditional methods. Therefore, this paper verifies this method through a concrete management system.